2015
DOI: 10.1182/blood-2014-02-557983
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor IRF8 plays a critical role in the development of murine basophils and mast cells

Abstract: Key Points IRF8 promotes Gata2 expression in GPs, thereby playing a key role in the development of basophils and mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…Moreover, the expression of Gata1, a transcription factor gene crucial for eosinophil development, is reduced in Irf8 −/− EoPs [49]. More recently, we found that Irf8 −/− mice are basophil deficient [17]. Basophils are the least common granulocytes circulating in peripheral blood, but their critical roles in Th2-type immunity and allergic disorders have been recently clarified.…”
Section: Regulation Of Eosinophil Basophil and Mast Cell Developmenmentioning
confidence: 85%
See 4 more Smart Citations
“…Moreover, the expression of Gata1, a transcription factor gene crucial for eosinophil development, is reduced in Irf8 −/− EoPs [49]. More recently, we found that Irf8 −/− mice are basophil deficient [17]. Basophils are the least common granulocytes circulating in peripheral blood, but their critical roles in Th2-type immunity and allergic disorders have been recently clarified.…”
Section: Regulation Of Eosinophil Basophil and Mast Cell Developmenmentioning
confidence: 85%
“…We found that Gata2, which encodes a transcription factor known to promote basophil differentiation, is induced by IRF8 in GPs and crucially acts downstream of IRF8 (Fig. 3) [17].…”
Section: Regulation Of Eosinophil Basophil and Mast Cell Developmenmentioning
confidence: 99%
See 3 more Smart Citations